Analisis Implementasi Profil Pelajar Pancasila Dampak Korupsi Bantuan Sosial Terhadap Kasus Kelaparan di Desa Curug Sangereng Tahun 2021 - Ananda Putriani; Widya Astuti (Departement of Mathematics Education, 2023)
Study this aim for analyze impact corruption help social to case hunger in Curug Sangereng Village in 2021. The method used in this study is method study qualitative descriptive with technique analysis content. Approach which conducted on study this is with method analyze object study then describe it. Analysis qualitative focus for show meaning, description, clearing, and placement data in the context each and often time write it down in shape words. Data the taken from results interview which conducted with Public in Village waterfall Sangereng. Results study this show that there is still corruption when distributing social assistance in Curug Sangereng Village. One of actions that are still happening are cutting social assistance funds given to residents. Consequence from cutting this, ability inhabitant for fulfil his needs Becomes reduce so that increase number starving. For resolve problem this, needed exists application education religion and pancasila, formation institution anti- corruption, making regulation about corruption, as well as enforce action repressive. Based on the results of these studies, it was concluded that social assistance and aid corruption social effect on survival Public.